Producing Hong Kong film genres for global consumption: Milkyway Image, 1996 to the present - Sun, Yi (2017)
The history of the Hong Kong-based film production company Milkyway Image from its inception in 1996 to present day examplifies the metamorphosis of the contemporary Hong Kong film industry to an era characterised by Hong Kong’s integration into a Chinese national context and the transnationalisation of world cinema. Drawing upon literature that studies film companies, this thesis adopts an integrative research framework that primarily combines industrial and discourse analysis to investigate Milkyway from a range of perspectives. It looks into the company’s ownership and organisational structure and the constitution of its creative team, comparing its similarities and differences to previous Hong Kong film companies and discussing how Milkyway bases itself on contemporary industry and its production models, business experiences and human resources from established studios such as the Shaw Brothers. Secondly, I explore Milkyway’s business and production practices in Hong Kong and mainland China by examining its genre films, including crime thrillers and romantic comedies, illustrating the Hong Kong film industry’s cooperation, negotiation and resistance in the process of Hong Kong cinema’s mainlandisation post-transfer of Hong Kong’s sovereignty from Britain to China. I then examine the discourse regarding Milkyway both inside and outside of Hong Kong, focussing on how the company and its work are received by various players in the film industry and community. The Hong Kong cultural community’s interpretations of Milkyway’s films represent an effort to maintain local cinema’s independence and local culture’s autonomy. International cultural bodies, such as film festivals, distributors and critics, receive Milkyway’s productions against the background of the increased globalisation of cinema and the development of the film industry and film institutions. Milkyway’s image changes as the company’s films travel across contexts and as various cultural forces provide multiple understandings of contemporary Hong Kong cinema. In shaping the discourse about Milkyway and its work, the company plays an active role by taking advantage of transnational platforms, such as film festivals, and interacting with film journalism and academia.